Integrated Marketing Communication Strategies through the Pentahelix Model for Tourism Village Development - Ayu Astutika Lestari; Supriyono Supriyono; Sutono Sutono (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study explores integrated marketing communication strategies for tourism village development by employing the Pentahelix model as an analytical framework. The research addresses challenges of limited stakeholder synergy and weak integration of marketing strategies. The objectives are to examine the roles of Pentahelix stakeholders—government, academia, community, business, and media—in shaping tourism communication; to identify internal and external factors influencing the effectiveness of marketing communication; and to formulate strategies for sustainable and competitive growth. A qualitative approach was adopted, utilizing in-depth interviews, participatory observation, documentation, and SWOT analysis. Findings reveal that stakeholder collaboration has established a moderately effective communication ecosystem, with the government acting as facilitator, academia as innovator, community as primary driver, business as economic enabler, and media as promotional catalyst. Nevertheless, challenges persist in coordination, human resource capacity, and fragmented information systems. SWOT analysis positions tourism villages in a strategic quadrant for aggressive growth. Recommended strategies include optimizing digital promotion, strengthening inter-village collaboration, fostering private sector partnerships, and enhancing marketing capacity and integrated information systems. This research contributes to the literature on tourism communication and provides practical guidance for tourism village managers in designing effective and sustainable marketing communication strategies.